Acceptability of human papillomavirus vaccines among women older than 26 years. Issue 13 (24th March 2015) - Dempsey, Amanda F.; Brewer, Sarah E.; Pyrzanowski, Jennifer; Sevick, Carter; O'leary, Sean T.
Abstract Objective To examine older women's (>26 years) acceptance of the human papillomavirus (HPV) vaccine, and factors associated with this outcome. Study design A convenience sample of 872 women age 26–77 years were surveyed regarding the likelihood they would accept the HPV vaccine if offered to them by their provider, and factors associated with this outcome. Binomial regression, Chi square and MacNemar's analyses were used to determine associations of this outcome with demographic, attitudinal, and experiential variables. Results The response rate was 60.8%. Half the respondents indicated they would want the vaccine, even if they had to pay for it. In multivariable analyses, the only factor associated with wanting the vaccine was higher self-reported knowledge about HPV (risk ratio 1.43, 95% Confidence Interval 1.12, 1.83). A majority of participants also believed that older women in general would want the vaccine if it were covered by insurance. However, this perspective was significantly diminished if the vaccine had to be paid for out of pocket (97% vs. 22% for 26–45 year olds; 84% vs. 20% for 46–65 year olds, 60% vs. 8% for 66+ year olds, p < 0.001). Nearly all (93%) believed primary care physicians should routinely discuss the vaccine with older women. Conclusions A high proportion of women over 26 would want the HPV vaccine if offered by their provider, even if they had to pay for it out of pocket. This suggests that if providers were to routinely offer the HPV vaccine to their older patients, many women would choose to get vaccinated.